Chemical Characteristics, with particular reference to phosphorus, of the rivers draining into Lake Naivasha, Kenya - Mavuti, Kenneth (School of Biological Sciences, 2002)
Macrophytes have been shown to perform important ecological roles in Lake Naivasha. Consequently, various studies regarding the impact of biotic factors on the macrophytes have been advanced but related studies on environmental parameters have lagged behind. In an attempt to address this gap, sampling on floating species and submergents was carried out in eight sampling sites in 2003 to investigate how they were influenced by a set of environmental factors. Soil texture (sandy sediments; P < 0.05, regression coefficient = - 0.749) and wind were the most important environmental parameters influencing the distribution and abundance of floating macrophytes. Combination of soil texture and lake-bed slope explained the most (86.3%) variation encountered in the submergents. Continuous translocation of the floating dominant water hyacinth to the western parts by wind has led to displacement of the submergents from those areas. In view of these findings, the maintenance and preservation of the steep Crescent Lake basin whose substratum is dominated by sand thus hosting most submergents remain important, if the whole functional purpose of the macrophytes is to be sustained.